Fatigue lifetime of rubber composites – State-of-the-art - Karolina Głowacka; Jernej Klemenc; Marko Nagode; Tadeusz Łagoda (Polymer Testing)
This paper reviews the literature regarding the fatigue strength of rubber composites - with particular emphasis on using rubber as a matrix. Various forms and materials of rubber reinforcement in rubber-based composites were analyzed. The use of 'classic' reinforcements, such as glass, carbon, or aramid fibers, was especially considered. It was noted that carbon reinforcement can take place in various forms - not only in the form of fibers but also, for example, carbon black. Literature data on rubber reinforcement with plastics, silica, or metal elements, e.g., for the production of tires, were analyzed. What is essential from the point of view of ecological aspects is the possibility of strengthening rubber, being a natural material, with natural additives derived from plants. It was observed that in rubber composites, the reinforcement occurs not only in the form of short or granular fibers but also in the form of continuous fibers – especially in the form of cords. The paper focuses on the analysis of the fatigue properties of these composites, identifying the location of the crack and its path, the course of the hysteresis loop, the dependence between and strain under cyclic loading of these materials, and also the computational models used in the fatigue analysis of rubber-based composites.